Asphyxiated Neonates Treated with Hypothermia: Birth Place Matters - Sabsabi, Bayane; Huet, Cloe; Rampakakis, Emmanouil; Beltempo, Marc; Brown, Richard; Lodygensky, Gregory A.; Piedboeuf, Bruno; Wintermark, Pia (American Journal of Perinatology, 2020)
Objective This study aimed to assess whether the hospital level of care where asphyxiated neonates treated with hypothermia were originally born influences their outcome.Study Design We conducted a retrospective cohort study of all asphyxiated neonates treated with hypothermia in a large metropolitan area. Birth hospitals were categorized based on provincially predefined levels of care. Primary outcome was defined as death and/or brain injury on brain magnetic resonance imaging (adverse outcome) and was compared according to the hospital level of care.Results The overall incidence of asphyxiated neonates treated with hypothermia significantly decreased as hospital level of care increased: 1 per 1,000 live births (109/114,627) in level I units; 0.9 per 1,000 live births (73/84,890) in level II units; and 0.7 per 1,000 live births (51/71,093) in level III units (p < 0.001). The rate of emergent cesarean sections and the initial pH within the first hour of life were significantly lower in level I and level II units compared with level III units (respectively, p < 0.001 and p = 0.002). In a multivariable analysis adjusting for the rates of emergent cesarean sections and initial pH within the first hour of life, being born in level I units was confirmed as an independent predictor of adverse outcome (adjusted odds ratio [OR] level I vs. level III 95% confidence interval [CI]: 2.13 [1.02–4.43], p = 0.04) and brain injury (adjusted OR level I vs. level III 95% CI: 2.41 [1.12–5.22], p = 0.02).Conclusion Asphyxiated neonates born in level I units and transferred for hypothermia treatment were less often born by emergent cesarean sections, had worse pH values within the first hour of life, and had a higher incidence of adverse outcome and brain injury compared with neonates born in level III units. Further work is needed to optimize the initial management of these neonates to improve outcomes, regardless of the location of their hospital of birth.Key Points
Keywords: brain; hypoxia-ischemia; level of care; neonatal encephalopathy; newborn; therapeutic hypothermia